Chemistry and biological activity of antitumour taxoids - Gueritte-Voegelein, Francoise; Guenard, Daniel; Dubois, Jane; Potier, Pierre (Malaysian Journal of Science, 2000)
Semi-synthetic approaches to paclitaxel, docetaxel and their derivatives were discussed. Their structure-activity relationship was also explained.